Kemampuan Pseudomonas Kelompok Fluorescens dalam Meningkatkan Ketahanan Tanaman Tomat Terhadap Infeksi Virus Keriting Kuning - Halimah, Nur; Aidawati, Noor; Fitriyanti, Dewi (JURNAL PROTEKSI TANAMAN TROPIKA, 2025)
This research uses Pseudomonas fluorescens which is thought to be able to inhibit disease populations and induce plant resistance. This research aims to determine the ability of the Pseudomonas fluorescens group to control yellow curl virus infection in tomato plants. This research used a Completely Randomized Design (CRD) with one factor consisting of five, namely 3 treatments, 1 control + treatment & 1 control, the treatments were repeated 4 times for a total of 20 plants. Each experimental unit contained 2 tomato plants for a total of 40 plants. The results of the research showed that Pseudomonas isolates from the flourescens group from bamboo, ferns and chilies were able to induce resistance in tomato plants to infection by the tomato yellow curl virus and only isolates from the Pseudomonas group from the flourescens group from ferns were able to stimulate the growth of tomato plants.